Analysis of Interactions Between ComponentsCatfish (Clarias batrachus), Mango (Mangifera indica), Banana (Musa paradisiaca), and Jabon (Neola-marckia cadamba) and Their Relationship to Pest Dynamic in Agrosilvopastural System, Tamiajeng Village, Trawas, Mojokerto, Indonesia - Chairunnisa Faza Nabillah; Ardhia Pramesti Cahyani; Difa Eka Pranoto; Diah Budi Kusumawati; Firdi Ihza Rochman; Penta Suryaminarsih (Nusantara Science and Technology Proceedings, 2022)
Agrosilvopastoral is a type of agroforestry that combines woody and non-timber crops, as well as animal husbandry/fisheries components. The agroforestry pattern in Tamiajeng Village belongs to the agrosilvopastoral type with components of jabon trees, mango banana trees and catfish ponds. The survey results showed that there was an interaction between the components of the observed agrosilvopastoral. Jabon and manga trees serve as shade for catfish ponds because catfish eggs need shade to hatch. The observations also showed the presence of dominant plant-disturbing organisms, such as fusarium wilt on bananas and sooty mildew on manganese. Integrated and sustainable control can be carried out by removing banana plants that are affected by disease and are no longer producing and can be used as catfish feed because banana stems have a function as additional nutrition and prebiotics for catfish. Controlling sooty mildew disease can be done by increasing air humidity in the presence of fish ponds so as to suppress the spread of conidia Capnodium sp sooty mildew fungus on mango leaves. Fish pond water can also be used as organic fertilizer for plants because it contains elements of nitrogen and phosphorus.